Bill Clinton : New Gilded Age president - Maney, Patrick J., 1946- (University Press of Kansas, 2016)
Set in the ""New Gilded Age"" the book goes beyond personality and politics to examine the critical issues of the day such as healthcare and welfare reform, business and financial deregulation, economic and fiscal practice, and foreign affairs in a post-Cold War world.